Simultaneous passenger lymphocyte syndrome and multiple alloimmunization against donor's blood group antigens after liver transplantation. Issue 1 (31st March 2015) - Monfort, M.; Honoré, P.; Gothot, A.; Gérard, C.
<x xml:space="preserve">Abstract</x> Background If 'passenger lymphocyte syndrome' (PLS) is a well‐recognized complication in ABO‐mismatched solid organ transplantation, the coexistence of this reaction with recipient's alloimmunization against multiple antigens expressed on the residual red blood cells in the graft is less common and unpredictable. Methods The receiver of an ABO minor‐mismatch liver graft from a cadaveric donor developed haemolytic anaemia within 2 weeks after transplantation. The organ donor was of blood group O D+C+c+E+e+ K+k+ Le(a+b‐) and the recipient, A1 D‐C‐c+E‐e+ K‐k+ Le(a‐b‐). The donor and recipient were both tested for irregular antibodies. Elution was performed on the recipient's red blood cells (RBCs). Results None of the recipient and donor had irregular alloantibodies at the time of transplantation. On day 10, anti‐A antibodies were detected in the recipient's serum and eluted from his RBCs. At the same time, the patient developed multiple alloantibodies: anti‐D, anti‐C, anti‐E, anti‐K and anti‐Lea against the donor's erythrocyte antigens. Conclusion Although serological analysis and haemolytic parameters confirmed the diagnosis of PLS which required transfusion support, no sign of graft damage due to recipient's immune reaction was detected. This case illustrates the required follow‐up of the recipient after transplantation.